Andreucci, B. (2011). Labradores de frontera. La Guardia de Luján y Chivilcoy, 1780-1860. Rosario: Prohistoria, 240 p. - Canedo, Mariana (2014)
Fil: Canedo, Mariana. Universidad Nacional de Mar del Plata - CONICET.